2015
DOI: 10.3109/00498254.2015.1078522
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of oxidative stress and mitochondrial/lysosomal cross-talk in olanzapine cytotoxicity in freshly isolated rat hepatocytes

Abstract: 1. Olanzapine (OLZ) is a widely used atypical antipsychotic agent for the treatment of schizophrenia and other disorders. Serious hepatotoxicity and elevated liver enzymes have been reported in patients receiving OLZ. However, the cellular and molecular mechanisms of the OLZ hepatotoxicity are unknown. 2. In this study, the cytotoxic effect of OLZ on freshly isolated rat hepatocytes was assessed. Our results showed that the cytotoxicity of OLZ in hepatocytes is mediated by overproduction of reactive oxygen spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 58 publications
3
28
0
Order By: Relevance
“…Also decreased lipid peroxidation and glutathione depletion occurred. The end result of these changes was cell lysis [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Also decreased lipid peroxidation and glutathione depletion occurred. The end result of these changes was cell lysis [36] .…”
Section: Discussionmentioning
confidence: 99%
“…Al-Chalabi, et al [6] showed that olanzapine could improve plasma total antioxidant status (TAS) and alleviate lipid peroxidation damage. Eftekhari, et al [15] found, in animal experiments, that olanzapine induced oxidative stress and hepatocytotoxicity and associated with the CYP450 enzyme. Olanzapine and clozapine were recently thought to be more effective than risperidone, quetiapine, ziprasidone and haloperidol in resisting oxidation [16] .…”
Section: Schizophreniamentioning
confidence: 99%
“…The utilized doses for ROS scavengers (butylated hydroxytoluen (BHT) and α-tocopherol succinate), MPT pore sealing agents (trifluoperazine and carnitine), ATP generators (l-glutamine and fructose), lysosomotropic agents (methylamine and chloroquine) and CYP450 inhibitors (cimetidine and 4-methylpyrazole) were chosen from similar experiments that were done on rat hepatocytes. [24][25][26] We also investigated the aforementioned doses in our isolation system and perceived that they have maximal protective impacts on the cytotoxicity indicators (data not shown).…”
Section: Animal Care Isolation and Incubation Of Liver Cellsmentioning
confidence: 99%